Analysis of Factors Affecting the Performance of Apron Movement Control (AMC) Officers in Improving Monitoring of Foreign Object Debris (FOD) on the Air Side of Adi Soemarmo International Airport Solo - Nur Fatimah; Syifa Fauziah (Formosa Journal of Science and Technology, 2023)
This study aims to determine whether there are variables that affect the performance of Apron Movement Control (AMC) officers in increasing FOD monitoring at the Air Side of Adi Soemarmo International Airport, Solo. It used quantitative method. According to the research findings, the regression coefficient value of the AMC officer's performance variable is 0.735, which means that the influence of AMC officer's performance in increasing FOD supervision is positive. A significance value of 0.000 <0.0    5 which indicates that the performance of AMC officers has a significant influence on improving FOD supervision. The coefficient of determination is 98.2% and the remaining 1.8% is influenced by variables outside the research. Hypothesis testing shows that the performance factors of AMC officers influence the growth of FOD monitoring at the Air Side of Adi Soemarmo Airport, Solo. This was reinforced by the majority of respondents expressing their agreement, especially with regard to the knowledge possessed by AMC officers regarding good work and providing good work results.